SBRT for the Primary Treatment of Localized Prostate Cancer: The Effect of Gleason Score, Dose and Heterogeneity of Intermediate Risk on Outcome Utilizing 2.2014 NCCN Risk Stratification Guidelines - Bernetich, Matthew; Oliai, Caspian; Lanciano, Rachelle; Hanlon, Alexandra; Lamond, John; Arrigo, Stephen; Yang, Jun; Good, Michael; Feng, Jing; Brown, Royce; Garber, Bruce; Mooreville, Michael; et al. (Frontiers in Oncology, 2014)
Purpose: To report an update of our previous experience using stereotactic body radiation therapy (SBRT) for the primary treatment of prostate cancer, risk stratified by the updated NCCN version 2.2014, reporting efficacy and toxicity in a community hospital setting. Methods: From 2007 to 2012, 142 localized prostate cancer patients were treated with SBRT using CyberKnife. NCCN guidelines Version 2.2014 risk groups analyzed included very low (20%), low (23%), intermediate (35%), and high (22%) risk. To further explore group heterogeneity and to comply with new guidelines, we separated our prior intermediate risk group into favorable intermediate and unfavorable intermediate groups depending on how many intermediate risk factors were present (one vs. >one). The unfavorable intermediate group was further analyzed in combination with the high risk group as per NCCN guidelines Version 2.2014. Various dose levels were used over the years of treatment, and have been categorized into low dose (35 Gy, n=5 or 36.25 Gy, n=107) and high dose (37.5 Gy, n=30). All treatments were delivered in five fractions. Toxicity was assessed using Radiation Therapy Oncology Group criteria. Results: 5-year actuarial freedom from biochemical failure (FFBF) was 100%, 91.7%, 95.2%, 90.0% and 86.7% for very low, low, intermediate and high risk patients, respectively (NS). A significant difference in 5 year FFBF was noted for patients with Gleason score >8 vs. 7 vs. 5/6 (p=0.03) and low vs. high dose (p=0.05). T-stage, pretreatment PSA, age, risk stratification group and use of ADT did not affect 5-year FFBF. Multivariate analysis revealed Gleason score and dose to be the most predictive factors for 5-year FFBF. Conclusion: Our experience with SBRT for the primary treatment of localized prostate cancer demonstrates favorable efficacy and toxicity comparable to the results reported for IMRT in literature. Gleason score remains the single most important pretreatment predictor of outcome.